European Grouping of Territorial Cooperation – a legal form supporting cross-border cooperation in the European Union - Tomáš Malatinec; Ján Kyjovský (Juridical Tribune, 2019)
European Grouping of Territorial Cooperation (EGTC) is European legal form that can be established under the Regulation (EC) No. 1082/2006 on a European Grouping of Territorial Cooperation. This measure is a part of the European Union’s Cohesion Policy, which aims to gradually reduce regional disparities and promote economic, social and territorial cohesion. EGTC supports and facilitates the formalized cross-border cooperation between Member States of the European Union, as well as their regional and local public authorities. Cross-border cooperation, which is a part of the Cohesion Policy, focuses mainly on border regions, whose weakness is their periphery location. In connection with the creation of the EGTCs, Member States may adopt measures to support this legal form by their national legislation and practice. The aim of the article is to present EGTC in terms of the European material and formal sources of law that have prompted the emergence of this legal form and govern the conditions for its establishment. EGTCs have the predisposition to carry out various activities related to cross-border cooperation. The European legal framework allows the use of EGTCs as entities for implementation of cross-border public procurement.